2022
DOI: 10.1002/sd.2354
|View full text |Cite
|
Sign up to set email alerts
|

The importance of institutional differences among countries in SDGs achievement: A cross‐country empirical study

Abstract: Based upon the “quintuple helix” model (Carayannis et al., 2012; Carayannis & Campbell, 2010), this research analyzes whether the differences in the level of achievement of the Sustainable Development Goals (SDGs) among 64 countries worldwide can be explained by a series of 19 institutional variables related to five dimensions such as cultural orientation, economic development, the education‐labor system, the political‐legal system and innovation. Our results highlight the crucial role of public policies in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 109 publications
(200 reference statements)
1
14
0
Order By: Relevance
“…These results suggest that richer economies allocate greater resources to promote innovation, making it a key element in driving sustainable development. Such a finding is in line with those of Husted ( 2005 ), who claimed that countries with stronger economies have more developed institutional and social capacities for sustainability because their strong economies provide more technology and resources for sustainable initiatives (Baughn et al, 2007 ; Reverte, 2022 ). Sustainable development means reorienting the progress of knowledge and technology, which should be neither eliminated nor interrupted (Schneider et al, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that richer economies allocate greater resources to promote innovation, making it a key element in driving sustainable development. Such a finding is in line with those of Husted ( 2005 ), who claimed that countries with stronger economies have more developed institutional and social capacities for sustainability because their strong economies provide more technology and resources for sustainable initiatives (Baughn et al, 2007 ; Reverte, 2022 ). Sustainable development means reorienting the progress of knowledge and technology, which should be neither eliminated nor interrupted (Schneider et al, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…Social‐cultural and economic features can also set barriers to sustainability achievement, even more so on islands. Because culture is relatively stable (Reverte, 2022), programs promoting sustainability should be consistent with local customs. Douglas (2006) stresses that sustainability concepts rely on the assumption often proved incorrect of “societal consensus on resource utilization, management issues, and the causes of environmental problems.” Our case studies exemplify the social consensus dilemma that generates tensions and division amongst stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…It requires effort coordination and good governance. Indeed, studies show a link between political conditions (e.g., effective governance, political stability, freedom of expression, corruption control) and SDG achievement (Reverte, 2022). In sum, governance ineffectiveness challenges the possibility of implementing integrated policies and making the best use of ESs assessments and the SDGs.…”
Section: Cumulative Effects Of Sdgs and Synergies With Other Policy F...mentioning
confidence: 99%
“…In a study of 66 selected developing countries covering the period 1984-2019 by Azam et al (2021), it is concluded that good institutions play a pivotal role in boosting sustainable development. While using panel data for a sample of 64 developed and developed countries Reverte (2022) shows that most of the divergence among countries in SDGs attainment can be attributed to governance factors. Similarly, in assessing the key drivers of green growth for some South Asian countries, Ahmed et…”
Section: Governance and Sustainable Developmentmentioning
confidence: 99%